Application of SRF-PI Current Control in the Design of a Single-Phase Asymmetrical Inverter for Use in Weak Grid Environments - Almas Begum M.A.A; Gandhi Geerthana M; Siva Sakthiya M; P. Anand; Shagar Banu. M (International Journal on Human-Computing Studies, 2023)
The power stage circuit and control system of the ACHMI uses a dual-loop current control mechanism in the hybrid reference frame (HRF), a synchronous reference frame phase-locked loop (PLL), and a hybrid modulation technique to generate a multilevel output voltage. The complete ACHMI system's small-signal model is derived using a simple, step-by-step derivation approach. Small-signal analysis is used to linearize the ACHMI system, which yields a model of its impedance. In addition, a refined impedance stability criterion is developed and used to analyse the robustness of the system under investigation. By adjusting the PLL bandwidth, output power factor angle, and grid current reference signal amplitude in the presence of poor grid conditions, the ACHMI's stability can be evaluated. This research suggests a methodical design procedure for choosing the PLL proportional-integral (PI) controller to guarantee steady-state performance and dynamic response in an ACHMI system. Finally, the theoretical theory is verified by modelling and real findings from a scaled-down grid-connected ACHMI prototype system.